Talkshow Online sebagai Bentuk Peran MUI dalam Pemulihan Karakter Keluarga di Masa New Normal: Online Talkshow as a Form of MUI’s Role in Restoring Family Character in the New Normal Period - Masnawati, Masnawati; Haniah, Haniah; Madjid, Sitti Saleha; Santalia, Indo; Damayanti, Eka (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The research objective is to provide participants with provision, knowledge, and skills about the importance of maintaining attachment in the family, especially in the new normal era. The activity of the research was in the form of a talk show titled "Family Character and Covid-19 (Challenges and Hopes)" conducted by the Commission on The Empowerment of Women, Adolescents, and Families of the Indonesian Ulama Council (MUI). The number of participants who participated in the talk show was 556 people from different educational backgrounds, professions, and ages from various institutions in South Sulawesi. Data collection instruments use questionnaires distributed through Google Forms. Data is processed using descriptive analysis. This community service was considered to have a distribution of material that follows the theme. Furthermore, the participants stated that the material presented on the talk show was very in-depth, valuable, and relevant to their requirements. The material presented can resuscitate the participants on the importance of restoring family character in the new normal era.